Competency for the OR registered nurse - Stephens, Gloria (Operating Room Nurses Association of Canada Journal, 1990)
Competency requires knowledge for critical thinking and decision-making, plus skills which are process-oriented to perform the technical components of perioperative nursing. Both (knowledge and skills) are integral components of the nursing process. Competency, therefore, is defined as the knowledge, skills, and abilities necessary to perform functions of a professional registered nurse in the operating room, regardless of the practice setting. Competency is per- formance expectations.